An investigation into the occurrence of, and risk factors for, concurrent suspensory ligament injuries in horses with hindlimb proximal suspensory desmopathy. (8th October 2019) - Gruyaert, M.; Pollard, D.; Dyson, S. J.
Summary: Hindlimb proximal suspensory desmopathy (PSD) is a common cause of lameness or poor performance in horses and may occur alone or together with other suspensory ligament (SL) injuries in forelimbs or hindlimbs. The aims of this retrospective case‐control study (January 2009 to December 2018) were to describe the occurrence of, and identify risk factors for, concurrent SL injuries in horses with hindlimb PSD. Data concerning age, breed, sex, work discipline, height, bodyweight and work history were collected. Concurrent SL injuries were defined as forelimb proximal suspensory desmitis or SL branch injuries (≥grade 2 [0–3]) in any limb. Hindlimb PSD was graded mild, moderate or severe based on ultrasonography. Data were described, and multivariable logistic regression modelling was used to identify factors associated with concurrent SL injuries. Data were available for 923 horses with hindlimb PSD, 28.6% (n = 264) of which had concurrent SL injuries. Age category (≤5 years of age vs. ≥6 years of age; P = 0.008), bodyweight:height ratio (P = 0.001), breed (P = 0.05), symmetry vs. asymmetry of hindlimb PSD ultrasonography grade (P = 0.005) and asymmetry vs. symmetry of lameness grade (P = 0.02) were associated with concurrent SL injury in horses with hindlimb PSD. Compared with horses aged ≥ 6 years, younger horses (odds ratio [OR] 1.76; 95% confidence interval [CI] 1.2–2.7) were more likely to have concurrent SL injury. The risk for concurrent SL injuries increased for every unit increase in bodyweight:height ratio (OR 2.27; CI 1.4–3.7). Compared with Thoroughbred crosses, Warmblood crosses (OR 3.3, CI 1.4–7.8), Thoroughbreds (OR 2.9, CI 1.1–7.1) and Irish Draught Horses (OR 3.5, CI 1.3–9.9) were more likely to have concurrent SL injuries. Hindlimb PSD ultrasonography grade severity was not associated with concurrent SL injury. In conclusion, age, bodyweight:height ratio and breed influenced the risk for concurrent lesions of the SL ligament. Further prospective studies in young horses are warranted.